Web-Based Decision Support System for Employee Performance Evaluation at Madani Hotel Using the WASPAS (Weighted Aggregated Sum Product Assessment) Method - Telaumbanua, Louders Yoakim; Saragih, Rendy Zikriansyah Fauzi; Ginting, Joel Arie Putranta; Niska, Debi Yandra (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2025)
Human resource management in the hospitality industry requires an objective and efficient employee performance evaluation. This study aims to design and implement a web-based Decision Support System (DSS) for evaluating the performance of Madani Hotel employees using the Weighted Aggregated Sum Product Assessment (WASPAS) method. Employee performance data (10 samples) were collected through observation and supervisor assessments based on nine criteria: Accuracy of Doing Job, Job Knowledge, Potential to Learn to Other Section, Initiative/Motivation, Hard Working, Able to Communicate with Others, Discipline, Productivity/Efficiency, and Responsibility. The weights of the criteria were determined based on their relevance to the job and were then normalized. The WASPAS calculation process was carried out in the CodeIgniter 4 backend, producing a Q score for each employee. The results showed a high correlation (Spearman’s rho = 0.88) between the system ranking and manual ranking, with A.P. ranked highest and E.W. ranked lowest. The implementation of this DSS reduces subjectivity and accelerates the performance evaluation process. The developed system also provides an automated reporting module and a responsive interface based on Bootstrap SAdmin2.